2017
DOI: 10.3892/etm.2017.5110
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of linolenic acid and tobramycin on Pseudomonas aeruginosa biofilm formation and quorum sensing

Abstract: Pseudomonas aeruginosa is a ubiquitous Gram negative opportunistic pathogen capable of causing severe nosocomial infections in humans, and tobramycin is currently used to treat P. aeruginosa associated lung infections. Quorum sensing regulates biofilm formation which allows the bacterium to result in fatal infections forcing clinicians to extensively use antibiotics to manage its infections leading to emerging multiple drug resistant strains. As a result, tobramycin is also becoming resistant. Despite extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 70 publications
(90 reference statements)
0
24
0
Order By: Relevance
“…A much higher concentration of 5 mg mL −1 of linoleic acid was necessary for a reduction in the biofilm formation of Pseudomonas aeruginosa and for the reported induced memory response during infection of the model host Galleria mellonella [25]. Some fatty acids such as linolenic acid combined with tobramycin were reported to interfere at higher concentrations with quorum sensing and inhibited the biofilm formation of P. aeruginosa [34]. Soni et al reported the inhibition of the quorum-sensing autoinducer-2 in their model system Vibrio harveyi BB170 by linoleic acid, oleic acid, palmitic acid and stearic acid at concentrations of 250 µm mL −1 or higher [35].…”
Section: Discussionmentioning
confidence: 99%
“…A much higher concentration of 5 mg mL −1 of linoleic acid was necessary for a reduction in the biofilm formation of Pseudomonas aeruginosa and for the reported induced memory response during infection of the model host Galleria mellonella [25]. Some fatty acids such as linolenic acid combined with tobramycin were reported to interfere at higher concentrations with quorum sensing and inhibited the biofilm formation of P. aeruginosa [34]. Soni et al reported the inhibition of the quorum-sensing autoinducer-2 in their model system Vibrio harveyi BB170 by linoleic acid, oleic acid, palmitic acid and stearic acid at concentrations of 250 µm mL −1 or higher [35].…”
Section: Discussionmentioning
confidence: 99%
“…They identified that adjuvant interactions between analogs and antibiotics successfully reduced the production of virulence factors in P. aeruginosa by controlling the QS system. Chanda et al revealed that linoleic acid, a natural fatty acid from ginger extracts, improved the potency of tobramycin when added together in P. aeruginosa biofilms ( 41 ). They confirmed that combined treatment downregulated QS system-associated gene expression more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Chanda et al 134 showed that linolenic acid and tobramycin (LNA+TOB) had significant impacts on downregulating the QS-mediated genes. Also, they have revealed that LNA+TOB therapy could inhibit motility phenotypes and reduce the development of infection.…”
Section: Synergism Between Qsis and Antibioticsmentioning
confidence: 99%